Hubungan Perceived Parental Conflict During Childhood Terhadap Perkembangan Gangguan Kecemasan Pada Dewasa Awal - Andi Nurul Ainy Azzahra; Rizki Dawanti (Universitas Mercu Buana, 2025)
Anxiety disorders are among the most common mental health problems, with a global prevalence of 301 million cases reported by WHO in 2019. Early adulthood is marked by various life demands that increase vulnerability to psychological problems, including anxiety. One contributing risk factor is childhood experience, particularly the perception of parental conflict. This study aims to examine the relationship between perceived parental conflict during childhood and anxiety disorders in early adulthood. This quantitative correlational study involved 152 early adults aged 18–40 years living in Tangerang who had witnessed parental conflict during childhood. The instruments used were the Children’s Perception of Interparental Conflict (CPIC) scale and the Generalized Anxiety Disorder-7 (GAD-7). Pearson correlation analysis showed a significant positive relationship between perceived parental conflict and anxiety levels in early adulthood.